1977
DOI: 10.1111/j.1529-8817.1977.tb02881.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOSYNTHESIS IN THE SNOW: THE ALGACHLAMYDOMONAS NIVALIS(CHLOROPHYCEAE)1

Abstract: Red blooms of snow algae consisting almost exclusively of large spherical red cells of Chlamydomonas nivalis (Bauer) Wille are widespread during the summer in the Beartooth Mountains in Montana and Wyoming. Field studies designed to examine the effects of temperature, light, and water potential on algal activity were performed with natural populations using photosynthetic 14C‐HCO3‐ or 14CO2 incorporation as a measure of activity. The algae photo‐synthesized optimally at 5.4 × 104 lx, but were not inhibited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
2

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 17 publications
1
27
2
Order By: Relevance
“…C. nivalis is apparently global, as it has been reported from New Zealand (1), Australia (2), and Europe (3)(4)(5)(6). In North America, it occurs in Alaska (5), the Cascade Mountains of the Pacific Northwest (7,8), the Sierra Nevada of California (7,9), and the Rocky Mountains of the western United States and Canada (7,10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C. nivalis is apparently global, as it has been reported from New Zealand (1), Australia (2), and Europe (3)(4)(5)(6). In North America, it occurs in Alaska (5), the Cascade Mountains of the Pacific Northwest (7,8), the Sierra Nevada of California (7,9), and the Rocky Mountains of the western United States and Canada (7,10,11).…”
mentioning
confidence: 99%
“…Thomas also reported that subsurface samples, which received less light, photosynthesized more than samples from the surface, suggesting that photoinhibition might have occurred in the surface layers. Mosser et al (10), however, reported no photoinhibition up to 8.5 ϫ 10 4 lux (Ϸ1,600 mol⅐m Ϫ2 ⅐s Ϫ1 ). Mosser et al (10) also studied the effects of temperature on 14 CO 2 uptake, finding that most populations had temperature optima between 10°C and 20°C.…”
mentioning
confidence: 99%
“…Earlier studies used different methods ( 14 C incubation or CO 2 gas exchange) and, with one exception (a study of a few green snow species in the former Czechoslovakia, Koma´rek et al, 1973), were carried out on algae from other continents, such as North America (Thomas, 1972;Mosser et al, 1977;Thomas & Duval, 1995;Williams et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Red snow algae have been described from both Antarctica and the arctic (Newton, 1982;Nicholas et al, 1990), North Finland Eurola, 1973, 1974), east Greenland (Fjerdingstad et at., 1974;Koshima, 1991), the Alaskan arctic (Kobayashi, 1967), and Japan (Fukushima, 1963;Kobayashi and Fukushima, 1952). Most of the red snow algae species collected from various regions have been classified and determined as Chlamydomonas nivalis (chlorophyceae; chlorophyta volvocales) (Mosser et al, 1977;Newton, 1982;Fjerdingstad et al, 1974;Kobayashi, 1967). Red blooms of snow algae consisting almost exclusively of large spherical red cells of Chlamydomonas nivalis are widespread only during the summer months.…”
Section: Introductionmentioning
confidence: 99%